2021
DOI: 10.2478/orga-2021-0001
|View full text |Cite
|
Sign up to set email alerts
|

Silence in Aviation: Development and Validation of a Tool to Measure Reasons for Aircraft Maintenance Staff not Reporting

Abstract: Background and purpose: Organizational silence, seen as the greatest obstacle to the success of organizations and expressed as a refraining from expressing feelings, and ideas about problems encountered in their organizations, is identified as the avoidance of voluntary reporting in aviation organizations. The main purpose of this research is to identify and develop a tool to measure the various reasons for aviation employees’ remaining silent about the unsafe acts and events they witness, and the factors caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Previous studies also have found the belief of don't embarrass the boss in public and negative career consequences of voice as a predictor of employee silence. For example, Under and Gerede, (2021) and Milliken et al (2003) stated that fear is one of the most important factors in employee silence. According to the qualitative study conducted with forty employees by Milliken et al (2003), the main reasons why the employees avoid expressing their opinions about the problems are their fear and their beliefs based on these fears.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies also have found the belief of don't embarrass the boss in public and negative career consequences of voice as a predictor of employee silence. For example, Under and Gerede, (2021) and Milliken et al (2003) stated that fear is one of the most important factors in employee silence. According to the qualitative study conducted with forty employees by Milliken et al (2003), the main reasons why the employees avoid expressing their opinions about the problems are their fear and their beliefs based on these fears.…”
Section: Discussionmentioning
confidence: 99%
“…Employees remain silent, believing that it is not worth talking about the problems within the organization or that expressing their opinions will endanger them (Under and Gerede, 2021). Fear of receiving negative feedback from managers and avoiding opposing situations cause them to remain silent (Morrison and Milliken, 2000).…”
Section: Employee Defensive Silencementioning
confidence: 99%
“…This study was included as it brings out a rather unusual hazard related to a language, as many safety occurrences are associated with misinterpretation and miscommunication of maintenance instructions. Under and Gerede (2021), studied the numerous reasons for employees' silence in aircraft maintenance organizations. Silence in this context means that employees are not reporting to the higher management the hazardous conditions, acts, and other such things having the potential to jeopardize the safety they observe in their functioning at the workplace.…”
Section: Organizational Influencesmentioning
confidence: 99%
“…In contrast, voluntary reporting is directly from the front-line maintenance staff they encounter while performing aircraft maintenance activities on a day-to-day basis. When investigated, this anonymous or confidential reporting system provides safety information about the organization's latent unsafe conditions or acts without legal and administrative obligations [25,27]. A voluntary reporting mechanism offers learning opportunities to maintenance staff and aircraft maintenance organizations without suffering severe consequences if effectively and efficiently exercised [28].…”
Section: Regulatory Framework and Lpsismentioning
confidence: 99%